Health workers' support for hepatitis C treatment uptake among clients with a history of injecting. (July 2018) - Brener, Loren; von Hippel, Courtney; Wilson, Hannah; Hopwood, Max
Hepatitis C virus is stigmatised because of its association with injecting drug use. Although treatment is available, uptake remains low, especially among people who inject drugs. Ninety health workers completed a survey assessing attitudes towards people who inject drugs and support for treatment for three client scenarios: one who stopped injecting, one on methadone, and one continuing to inject. Support for hepatitis C virus treatment was significantly higher, where the client was not injecting. Participants who showed more negative attitudes towards people who inject drugs were less supportive of clients entering hepatitis C virus treatment, illustrating the influence of health workers' attitudes in determining treatment options offered to clients.